KARDIOMIOPATI PADA INFEKSI HIV - Rampengan, Starry H. (Jurnal Biomedik : JBM, 2011)
Abstract: Heart muscle involvement associated with human immunodeficiency virus (HIV) infection may be seen as myocarditis, dilated cardiomyopathy, or as an isolated left or right ventricular dysfunction. Histopathological and ultra structural findings with different degrees of cardiac-chamber dilation have been described, and important roles of cytokines (tumor necrosis factor-alpha, interleukin-1, and interleukin-6) have been suggested. HIV infection is an important cause of dilated cardiomyopathy, with a prevalence of 3.6% among cardiomyopathy patients that live longer. HIV patients with dilated cardiomyopathy have a much worse prognosis than those with idiopathic dilated cardiomyopathy (hazard ratio of death 4.0). HIV related myocardial dysfunction may easily be overlooked due to attributing symptoms such as breathlessness, fatigue, respiratory diseases, or anaemia. The diagnosis is readily made by echocardiography which can show dilatation or impaired contractility, or both of either or both ventricles. Isolated right ventricular dysfunction can be caused by cardiomyopathy, pulmonary hypertension secondary to repeated respiratory infections, thromboembolic diseases, or recurrent pulmonary emboli from intravenous debris acquired through drug abuse. Endomyocardial biopsy in patients with heart failures associated with HIV infection has been performed in several centers, and has identified myocarditis caused by potentially treatable infections due to organisms such as toxoplasma gondii. Keywords: Cardiomyopathy, HIV infection, myocarditis, management.Â Â  Abstrak: Keterlibatan kerusakan jantung pada pasien human immunodeficiency virus (HIV) biasanya dalam bentuk miokarditis, kardiomiopati dilatasi, ataupun disfungsi ventrikel kiri atau kanan terisolasi. Penemuan histopatologik dan ultrastruktur menunjukkan perbedaan derajat dilatasi ruang-ruang jantung dipengaruhi oleh peranan beberapa jenis sitokin (tumor necrosis factor-alpha, interleukin-1 dan interleukin-6). Infeksi HIV merupakan penyebab utama terjadinya kardiomiopati dilatasi dengan prevalensi 3,6% dari antara penderita kardiomiopati yang hidup lama. Infeksi HIV dan kardiomiopati dilatasi memiliki prognosis yang jauh lebih buruk dibandingkan dengan penderita kardiomiopati dilatasi yang idiopatik. Disfungsi miokard dalam kaitannya dengan HIV lebih mudah diidentifikasi karena adanya gejala yang jelas seperti sesak napas, mudah capek, penyakit saluran napas ataupun anemia. Hal tersebut diatas menyingkirkan kemungkinan akibat terapi paliatif dari pasien HIV. Diagnosis pasti dilakukan dengan pemeriksaan ekokardiografi, dimana terlihat dilatasi ataupun perburukan kontraktilitas jantung maupun akibat dari keduanya, atau terjadi pada kedua ventrikel. Disfungsi ventrikel kanan terisolasi dapat diakibatkan karena kardiomiopati, juga hipertensi pulmonal sekunder oleh karena infeksi saluran napas berulang, penyakit tromboemboli maupun emboli paru berulang dari debris intravena pada pecandu narkoba. Di beberapa pusat jantung telah dilakukan biopsi endomiokard pada pasien gagal jantung dengan infeksi HIV, dan diidentifikasi penyebab tersering yang dapat diobati adalah miokarditis dengan organisme seperti toxoplasma gondii. Kata Kunci: Kardiomiopati, infeksi HIV, miokarditis, tatalaksana.